Challenges in the synthesis of corannulene-based non-planar nanographenes on Au(111) surfaces. Issue 18 (28th April 2021) - Wang, Tao; Lawrence, James; Sumi, Naoya; Robles, Roberto; Castro-Esteban, Jesus; Rey, Dulce; Mohammed, Mohammed S. G.; Berdonces-Layunta, Alejandro; Lorente, Nicolas; Pérez, Dolores; Peña, Diego; Corso, Martina; et al.
Abstract : The on-surface synthesis of corannulene-based non-planar nanographenes was studied with the aid of bond-resolving scanning tunneling microscopy. Abstract : The on-surface synthesis of non-planar nanographenes is a challenging task. Herein, with the aid of bond-resolving scanning tunneling microscopy (BRSTM) and density functional theory (DFT) calculations, we present a systematic study aiming at the fabrication of corannulene-based nanographenes via intramolecular cyclodehydrogenation on a Au(111) surface. The formation of non-planar targeted products is confirmed to be energetically unfavorable compared to the formation of planar/quasi-planar undesired competing monomer products. In addition, the activation of intermolecular coupling further inhibits the formation of the final targeted product. Although it was not possible to access the corannulene moiety by means of on-surface synthesis, partial cyclodehydrogenation of the molecular precursors was demonstrated.